Decoding tau acetylation in Alzheimer’s disease and tauopathies: from site-specific mechanisms to therapeutic horizons - Yoonah R. Oh; Min-kyoo Shin (BMB reports, 2025)
Tau acetylation has been recognized as a pivotal post-translational modification associated with the pathogenesis of Alzheimer’s disease (AD) and other tauopathies. This review offers a detailed synthesis of the current understanding of site-specific tau acetylation, its regulatory enzymes, and its profound impacts on tau biology. Acetylation influences tau degradation, aggregation, propagation, and microtubule-binding properties in a residue-specific manner, often in conjunction with other modifications such as phosphorylation and ubiquitination. Furthermore, this review emphasizes emerging therapeutic strategies targeting tau acetylation, including small-molecule inhibitors of p300/CBP and monoclonal antibodies against acetylated tau epitopes. While several of these approaches are currently undergoing clinical trials, many acetylation sites are still inadequately characterized, emphasizing the need for additional mechanistic studies. An enhanced understanding of tau acetylation will be vital for devising targeted therapies to halt or reverse the progression of tau-mediated neurodegeneration. [BMB Reports 2025; 58(8): 325-339]